Open reduction and K-wiring of severely displaced supracondylar humerus fracture in children:Comparison between posterior triceps splitting approach and lateral approach - Vasan , Sinnadurai (2001)
This is a retrospective study of patients treated with open reduction and internal fixation of a severely displaced supracondylar fracture humerus in children. Open reduction and internal fIXation with k-wire for displaced supracondylar fracture of the humerus is practiced widely in many centers. Various approaches and techniques for open reduction of this type of fracture have been described by various authors. (Ramsey and Griz 1973,Carcassonne et al1972) In Hospital lpoh, posterior or lateral approach is commonly used . All patients treated with open reduction and k-wiring in Hospital lpoh from January 1997 till April 1998 were reviewed. Out of total patients operated during the study period, 36 returned for final follow-up. They were re-examined to assess the functional outcome, range af motion and incidence of cubitus varus of the affected elbow, as well as surgical and cosmetic complications. The posterior approach group was noted to have higher incidence of surgical complications eg cubitus varus defonnity and reduced range of elbow motion. This also included nerve injury, failure to achieve good reduction at first attempt of open reduction and unsightly scar and painful scar. Those patients who were operated by lateral approach had a better result and fewer complications.